2021
DOI: 10.1021/acsomega.0c05845
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Commercial Iron Oxide Nanoparticles: Structural and Magnetic Property Characterization

Abstract: Magnetic nanoparticles (MNPs) have been extensively used as tiny heating sources in magnetic hyperthermia therapy, contrast agents in magnetic resonance imaging (MRI), tracers in magnetic particle imaging (MPI), carriers for drug/gene delivery, etc. There have emerged many magnetic nanoparticle/microbeads suppliers since the last decade, such as Ocean NanoTech, Nanoprobes, US Research Nanomaterials, Miltenyi Biotec, micromod Partikeltechnologie GmbH, and nanoComposix, etc. In this paper, we report the physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Since they can be synthesized in variety of sizes and shapes and further manipulated through external magnetic fields, magnetite nanoparticles (MNPs) can be employed in magnetic resonance imaging and magnetic particle imaging as imaging contrast enhance ment agents; targeted delivery of bioactive molecules, drugs, antibodies, nucleic acids, and proteins; hyperthermia for cancer treatment; cell separation and detection; biosensing and immunoassays; tissue repair; and body fluid detoxification [ 1 , 8 , 9 , 10 , 11 ]. Additionally, MNPs have demonstrated their potential in oil recovery, catalysis, and water remediation applications [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since they can be synthesized in variety of sizes and shapes and further manipulated through external magnetic fields, magnetite nanoparticles (MNPs) can be employed in magnetic resonance imaging and magnetic particle imaging as imaging contrast enhance ment agents; targeted delivery of bioactive molecules, drugs, antibodies, nucleic acids, and proteins; hyperthermia for cancer treatment; cell separation and detection; biosensing and immunoassays; tissue repair; and body fluid detoxification [ 1 , 8 , 9 , 10 , 11 ]. Additionally, MNPs have demonstrated their potential in oil recovery, catalysis, and water remediation applications [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…210 So far, no reported supplier or industry produced large-scale and commercial nanometer-sized iron oxides synthesized using the green approach, especially the utilization of biological substances as reduction and transformer agents, instead of industries that used convention methods, such as Ocean NanoTech, Nanoprobes, US Research Nanomaterials, Miltenyi Biotec, micromod Partikeltechnologie GmbH, nano-Composix, etc. 244 Nevertheless, it was reported that many industries also try to achieve more green approach in the nanomaterials productions, such as the replacement of volatile organic reduction and transformation agents, developing recyclable process, using energy-efficient synthesis and encouraging the use of renewable raw materials. 245 The abundance and large availability of iron ore or iron sands, as well as renewable iron wastes as a starting material in the production of nanometer-sized iron oxides, would support the realization of nanometer-sized iron oxides in the marketplace.…”
Section: Commercialization Of Nanometer-sizedmentioning
confidence: 99%
“…For instance, α-Fe 2 O 3 nanoparticles synthesized using green tea leaf extract exhibited higher photocatalytic activity, because of a higher surface area, compared to the commercial α-Fe 2 O 3 nanoparticles . So far, no reported supplier or industry produced large-scale and commercial nanometer-sized iron oxides synthesized using the green approach, especially the utilization of biological substances as reduction and transformer agents, instead of industries that used convention methods, such as Ocean NanoTech, Nanoprobes, US Research Nanomaterials, Miltenyi Biotec, micromod Partikeltechnologie GmbH, nanoComposix, etc . Nevertheless, it was reported that many industries also try to achieve more green approach in the nanomaterials productions, such as the replacement of volatile organic reduction and transformation agents, developing recyclable process, using energy-efficient synthesis and encouraging the use of renewable raw materials …”
Section: Commercialization Of Nanometer-sized Iron Oxides Through Gre...mentioning
confidence: 99%
“…45 The application of AMF toward magnetic filler was widely carried out to conduct hyperthermia to damage cancerous cells or tumors in the medical industry. 33,46,47 Although we did not measure the temperature, there is a possibility of localized heating or transfer of energy that may affect the densification of the polymer surrounding the magnetic fillers.…”
Section: Influence Of Membrane Magnetization On Gas Separation Perfor...mentioning
confidence: 99%